Design and early childhood education: proposal of an educational toy for preschool children - Cynthia Dias Bicalho; Poliana Pereira de Oliveira; Thiago Guimarães Azevedo (Projetica, 2019)
The purpose of this project is the design of an educational toy for preschool children, in order to improve their educational cognitive development, besides encouraging the participation of the designer in the creative process of educational toys. In order to do so – and based on the structuralist methodology – a bibliographical and documentary research was performed, prior to the conduction of interviews and participatory field observations in two preschool scenarios in Paragominas, Brazil. After comparing these data, the information was used in the first part of the Löbach project, which then served as the basis for the second part: the design of the Persona Card Game. Several ideas and proposals emerged in order to select the one closest to meet the project requirements. Finally, we present the educational toy itself, which not only promotes the development of educational cognitive aspects (based on Piaget’s theory), but also meets the needs of the educators interviewed.